How to integrate ports into the EU ETS: the CAS approach perspective - Ayaz, İlke Sezin; Bucak, Umur; Esmer, Soner (Emerald Publishing, 2024)
Purpose: The European Union's Emissions Trading System (EU ETS), which is already one of the EU's most impactful instruments for reducing greenhouse gases (GHGs), will soon include the maritime transport industry. Although ports are this industry's most environmental-friendly component, there are still some barriers to including ports in the system. Therefore, the purpose of the study is to identify these barriers and to reveal the barriers' interrelationships. Design/methodology/approach: The study was conducted by identifying barriers from a literature review before analyzing the barriers with the Fuzzy DEMATEL method. Finally, based on the Complex Adaptive System Approach, various solutions are proposed to overcome these barriers. Findings: The identified barriers were grouped into cause-and-effect groups. Two barriers, namely long payback period and high investment costs, were evaluated as triggers of the model while the others were more sensitive to the model. Research limitations/implications: This study only includes the perceptions of green certificated ports in Türkiye. The results revealed an expectation that elimination of financial concerns will alleviate other barriers to including ports in the system. The study's findings can guide port managers on the integration of the managers' processes into the system. Originality/value: This study provides novel findings regarding the relationships between barriers hindering ports from involvement in the EU ETS. © 2023, Emerald Publishing Limited.
Keywords: Barriers; Complex adaptive system approach; Emissions trading system; Fuzzy DEMATEL; Ports